2021
DOI: 10.1002/pro6.1129
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for radiotherapy of prostate cancer (2020 edition)

Abstract: In recent years, the incidence of prostate cancer in China has shown a trend of continuous growth. Prostate cancer has become a urinary malignant tumor that seriously affects the health of men in China. Radical surgery and precision radiotherapy are the main methods of radical treatment for prostate cancer. Standardized diagnosis and treatment via a multidisciplinary team should be the standard practice to improve cure rate. Rapid development in imaging, pathology and molecular gene diagnosis has significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Even though cell lines are a unique tool to study the mechanisms behind the occurring radiosensitization due to AuNPs, it is crucial to discuss briefly how they might be utilized in either animal or human tumors. Depending on the type and stage of cancer, radiotherapy is usually applied in fractions giving in total 20–80 Gy [ 110 , 111 ]. One of the main side effects of cancer radiotherapy is that it cannot usually spare completely the nearby normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Even though cell lines are a unique tool to study the mechanisms behind the occurring radiosensitization due to AuNPs, it is crucial to discuss briefly how they might be utilized in either animal or human tumors. Depending on the type and stage of cancer, radiotherapy is usually applied in fractions giving in total 20–80 Gy [ 110 , 111 ]. One of the main side effects of cancer radiotherapy is that it cannot usually spare completely the nearby normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy to positive lymph nodes remains the standard of care in the treatment of metastatic prostate cancer, which was the case for this patient. [2][3][4][5] A systemic review of retrospective studies using IMRT/VMAT as adjuvant therapy for positive lymph nodes prostate cancer suggested a target dose of 45-60 Gy with boost dose as high as 70 Gy to high-risk areas. 6 The treatment plan for the lymph nodes in this patient was consistent with the plans used in atlas definition and other published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other indications include extra-prostatic and/or seminal vessel involvement and positive margins after prostatectomy. 5 However, guidelines on whether additional lymph nodes should be contoured and treated remain less well defined, especially in patients with node positive disease at presentation as the pattern of failure may be altered secondary to retrograde flow through pelvic lymphatic channels or interruption of tissue planes by surgery. As such, the decision to preemptively treat other lymph nodes typically remains up to the discretion and experience of the practitioner who will assign tissues at risk based on pre-determined guidelines of care.…”
Section: Introductionmentioning
confidence: 99%
“…Using low doses of radiation to gather CT images could cause long-term off-target effects in mice. However, the dose required for sub-millimeter resolution imaging is less than 1 centigray, which is far below the recommended dose of 76-80 gray for definitive prostate radiotherapy in humans or 5-7 gray whole body irradiation to result in mouse lethality [29,30]. These tumor bearing animals only live a month or two after irradiation, which will not provide them the time to potentially develop any of these side effects.…”
Section: Plos Onementioning
confidence: 99%